Dietary inflammation: a potential driver of atopic dermatitis?–Evidence from KNHANES 2017–2023 - Tan, Kaiyue; Sun, Nanren; Wang, Dongyang; Chen, Jiaojiao; Long, Jiaqi; Zhang, Junbin (Frontiers in Immunology, 2025)
BackgroundThe global incidence of atopic dermatitis (AD) has risen significantly in recent decades, with trends showing spatial and temporal coupling with dramatic changes in dietary habits during industrialisation. Although the Dietary Inflammatory Index (DII), a tool to quantify the inflammatory potential of diet, has made breakthroughs in the study of chronic inflammatory diseases, large-scale cross-sectional evidence for its association with AD is still lacking.MethodsBased on large-scale population-based cross-sectional data from Korean National Health and Nutrition Examination Survey(KNHANES)2017-2023, the association between DII quartiles and AD risk was analysed using weighted multivariate logistic regression, with adjusted odds ratios (aORs) and 95% CIs calculated, stratified by sex (male/female) and age (≤54 vs >54); interactions were assessed by the Wald test, and the association between dietary index and risk was assessed using the Restricted cubic spline(RCS) models (with nodes set at the 10th, 50th, and 90th percentiles of DII) were used to explore non-linear associations, with models adjusted for covariates such as sex, age, and education.ResultsHigher DII scores showed a significant association with AD prevalence. Participants in the highest DII quartile had a 73% higher risk than those in the lowest quartile (aOR = 1.73, 95% CI = 1.45-2.07).and the sex interaction was significant (interaction p<0.05), with stronger associations in the female group; RCS analyses showed a possible linear association between DII and AD risk (non-linear p>0.05).ConclusionHigh dietary inflammatory index was significantly and positively associated with high prevalence of AD, especially in female and younger age groups; Notably, higher intake of dietary fiber and carotene is associated with a lower prevalence of AD.